Computer Society Magazines: 2008 Preview. (Computer (00189162), 2007)
The article presents previews of upcoming content in 2008 for each of the 14 technical magazines published by the IEEE Computer Society. "Computer" magazine's January, 2008 issue will feature articles on virtualization, cybersecurity, and computational intelligence. Software quality, quantitative methods, and software development infrastructure will receive attention during 2008 in issues of "IEEE Software." The May/June issue of "IEEE Security & Privacy" will focus attention on electronic voting.